Balance dysfunction in adults with haemophilia - Fearn, M.; Hill, Keith; Williams, S.; Mudge, L.; Walsh, C.; McCarthy, P.; Walsh, M.; Street, A. (Blackwell Publishing Ltd, 2010)
The main focus of lower limb physical performance assessment in people with haemophilia (PWH) has usually been on function, muscle strength and joint flexibility. The impact of haemophilic arthropathy on balance and falls risk is relatively under-explored. The aim of this study was to evaluate balance and related performance in PWH compared with age and gender matched healthy controls. It involved a comprehensive suite of clinical and laboratory measures of static and dynamic balance, mobility, strength, physical activity and falls efficacy completed in 20 PWH (mean age 39.4, 100% male) and 20 controls. Fifty percent of PWH reported falls in the past 12 months. Moderate impairment of balance and related measures were identified in PWH compared with the controls, with an average 35% difference between groups. Significant differences were evident between groups on both clinical and laboratory measures, including measures of dynamic bilateral stance balance [limits of stability measures on the laboratory test, functional reach; (P < 0.001); dynamic single leg balance (Step Test, P < 0.001)], gait and mobility (gait speed, step width and turning measures on the laboratory test, timed up and go test; P < 0.001); muscle strength (timed sit to stand, P = 0.002; quadriceps strength, P < 0.001); and activity level and falls efficacy, (P < 0.004). The dynamic clinical and laboratory measures testing similar domains of balance, gait and mobility had moderate correlations (0.310 < r < 0.531, P < 0.01). Moderate impairments in balance, mobility and related measures were identified in PWH, compared with the control group. Clinicians should include assessments of balance and related measures when reviewing adults with haemophilia. © 2010 Blackwell Publishing Ltd.